EFFECTS OF A HEALTH BEHAVIOR MODIFICATION PROGRAM ON OVERWEIGHT PERSONNEL AT BUENGKAN HOSPITAL, BUENGKAN PROVINCE - จันทร์อ้วน สุกัญญา; อุ้ยวงค์ ภาวิณี (Primary Health Care Journal (Northeastern Edition), 2025)
Overweight and obesity among public health personnel pose significant health challenges and affect their ability to serve as role models for the community. This quasi-experimental study aimed to evaluate the effects of a health behavior modification program among hospital personnel with a body mass index (BMI) exceeding the standard threshold at Buengkan Hospital. The intervention was based on Social Cognitive Theory and Lifestyle Medicine principles. The sample consisted of 60 overweight personnel selected through simple random sampling. Participants were divided into an experimental group (n = 30), which received a 12-week health behavior modification program, and a control group (n = 30), which received standard follow-up care at the Disease Prevention and Control Clinic (DPAC). Data were collected using body composition assessment records and a health behavior questionnaire. Descriptive statistics included percentages, means, and standard deviations. Inferential statistics included Paired Sample t-tests and Independent t-tests. Results showed that, after the intervention, the experimental group had a significantly higher mean health behavior score compared to the control group (Mean Difference = 29.40, p < .001). Body composition indicators also improved significantly in the experimental group, including an average BMI reduction of 1.40 units, a waist circumference reduction of 7.99 cm, a decrease in body fat percentage by 7.63%, and an increase in muscle mass by 14.07 units. In conclusion, the health behavior modification program designed specifically for personnel with high BMI was effective in improving both health behaviors and body composition. It is recommended that this program be integrated into routine hospital health services or incorporated into health promotion policies for personnel to ensure organizational sustainability in structure and resources.